2017
DOI: 10.1002/pmic.201600215
|View full text |Cite
|
Sign up to set email alerts
|

A rapid differential display analysis of nasal swab fingerprints to distinguish allergic from non‐allergic rhinitis subjects by mesoporous silica particles and MALDI‐TOF mass spectrometry

Abstract: Discriminating different rhinitis cases can sometimes be difficult as the diagnostic criteria used to identify the various subgroups are not always unambiguous. The nasal fluid (NF) highly reflects the pathophysiology of these inflammatory diseases. However, its collection, as nasal lavage fluid, may cause discomfort. Due to the non-invasiveness and rapidity of collection, nasal swab might represent an alternative to overcome these problems and also an ideal source of biomarkers. In this study, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 67 publications
1
15
0
Order By: Relevance
“…Apart from NLF nasal secretions can be obtained for mass spectrometric analysis by nasal cotton swabs or filter papers. Preiano et al [84] and Lombardo et al [85] used cotton swabs and a fast procedure based on mesoporous silica particles (MPS) to enrich nasal fluids in its antimicrobial protein component in combination with MALDI-TOF/TOF MS to differentiate between healthy probands and patients with upper respiratory diseases like allergic rhinitis by proposing 'rhinomic fingerprints. ' Kim et al [86] applied filter paper in patients with CRS to collect nasal secretions for nanoLC-MS/MS on a quadrupole orbitrap mass spectrometer (Q-Exactive plus; Thermo Fisher Scientific).…”
Section: Proteomics Of the Nasal Mucusmentioning
confidence: 99%
“…Apart from NLF nasal secretions can be obtained for mass spectrometric analysis by nasal cotton swabs or filter papers. Preiano et al [84] and Lombardo et al [85] used cotton swabs and a fast procedure based on mesoporous silica particles (MPS) to enrich nasal fluids in its antimicrobial protein component in combination with MALDI-TOF/TOF MS to differentiate between healthy probands and patients with upper respiratory diseases like allergic rhinitis by proposing 'rhinomic fingerprints. ' Kim et al [86] applied filter paper in patients with CRS to collect nasal secretions for nanoLC-MS/MS on a quadrupole orbitrap mass spectrometer (Q-Exactive plus; Thermo Fisher Scientific).…”
Section: Proteomics Of the Nasal Mucusmentioning
confidence: 99%
“…We started with an initial study on a small cohort of patients with gingivitis ( n = 10) and a control group of healthy individuals ( n = 10) using samples either freshly processed or stored at −80 °C for less than 1 month. This one being a very preliminary study, no power calculations were performed to decide the sample size; however, groups of similar (even smaller) size recently allowed us to identify putative biomarkers of allergic and nonallergic rhinitis . The demographic as well as clinical characteristics of the subjects of this study are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analyses were performed using SPSS (version 11.5, Chicago, IL, USA) or Origin Pro (version 7.5, OriginLab Corporation, Northampton, MA, USA) software. Data from healthy and gingivitis groups, once pre‐processed, were subsequently analyzed for differential peptide patterns as previously described . In particular, for statistical analysis, peaks with a similar m / z value across all spectra (within 0.1%) were considered the same.…”
Section: Methodsmentioning
confidence: 99%
“…Within this context, proteomic and peptidomic techniques are emerging as highly valuable tools that can be applied to the analysis of nasal mucosa secretions. Standardized and reproducible samples of both nasal exudates and mucosal cells can be obtained in a relatively noninvasive manner such as nasal lavage, nasal swabs, filter paper strips, nasal brushing and scraping, and a nasal biopsy [1,7]. These specimens constitute a useful source of information for clinical-based and large-scale proteomics investigations.…”
Section: Introductionmentioning
confidence: 99%